2015
DOI: 10.3996/072013-jfwm-050
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Three Common Moist-Soil Managed Wetland Plant Species

Abstract: Moist-soil wetland management is used to precisely control delivery, duration, and timing of water addition to, and removal from, managed wetlands with targeted responses including germination and growth of desirable moist-soil plant species. Similarly, water delivery and removal drives decomposition of moist-soil plants as well as nutrient cycling within these systems, which is a key driver of productivity in such managed wetlands. Through deployment of litter bags, we examined rate of mass loss and decay coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The plant species that are adapted to these low-nutrient ecosystems can maintain positive population growth and add organic C to soils. Further, flooded environments, such as wetlands, are also known to support anaerobic microbial processes, which result in slower rates of decomposition (Collins et al 2015). Taken together, low-nutrient environments can be sites of long-term C storage in soils because of high plant biodiversity leading to organic C inputs and balanced with slower decomposition rates (Hooper et al 2005, Kleber et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The plant species that are adapted to these low-nutrient ecosystems can maintain positive population growth and add organic C to soils. Further, flooded environments, such as wetlands, are also known to support anaerobic microbial processes, which result in slower rates of decomposition (Collins et al 2015). Taken together, low-nutrient environments can be sites of long-term C storage in soils because of high plant biodiversity leading to organic C inputs and balanced with slower decomposition rates (Hooper et al 2005, Kleber et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Most decomposition information comes from farther south than this study area and, because decomposition may vary with latitude (Williams et al 2014), seeds in this study area may decompose less than published estimates from elsewhere. If seeds in this study area were losing at least 50% of their mass by 120 days as in Collins et al (2015), I would have observed substantially more depletion than what I observed. Depredation by non-ducks could also account for some of the depletion.…”
Section: Discussionmentioning
confidence: 53%
“…Hagy and Kaminski () estimated that Japanese millet ( Echinochloa frumentacea ) decomposed 8.9% every 2 weeks during winter in the Mississippi Alluvial Valley. In Texas, 3 species of moist‐soil plant seeds lost about 33% biomass during the first 45 days of decomposition and between 50% and 80% by 120 days (Collins et al ). Most decomposition information comes from farther south than this study area and, because decomposition may vary with latitude (Williams et al ), seeds in this study area may decompose less than published estimates from elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Areas become unsuitable for the white-winged flufftail when vegetation structure is degraded [28]. The effect of cattle grazing is also evident in the dispersal of the declared alien invader weed Persicaria lapathifolia, which easily establishes in disturbed areas where moist conditions prevail [32]. This weed, which is prominent within community 1.3 (Middelpunt Wetland), is normally introduced into peatlands through drainage water from adjacent cultivated lands or areas where cattle are fed.…”
Section: Discussionmentioning
confidence: 99%